Malay-Dusun dictionary : language translation application for daily conversation / Denver Christopher Gissong - Denver Christopher, Gissong (2013)
Language is very important in our daily life. Without language, no creatures in this world can communicate. Even animals have their own languages. For us as a human being, language represents our culture and race. Language must be continuously learned and taught so that the future generation can learn it. Therefore, this project development is about to make sure that Dusun Language, which is the native language for Kadazandusun ethnic in Sabah can stay being well-known although the world is getting old and manipulated by technology. This project is aim to develop a computer application that will translate Malay language to Dusun Language. Since there is not yet available, a computer application that can translates a sentence from Malay to Dusun language; this application will be the first electronic Dusun language references that can be utilized by the community.